Pengaruh Tingkat Kepercayaan Berkomunikasi di Jejaring Sosial Internet (Social Media) Terhadap Perilaku Beli Mahasiswa: Survei Asosiatif Netter Kaskus Mahasiwa Jurusan Teknologi Informasi di beberapa Kampus di Jakarta - Ilham Prisgunanto (Universitas Multimedia Nusantara, 2012)
The research examines effect of the confidence level of students in social media to communicate to their buying behavior. The theories used in this research are impersonal interpersonal communication model develop by Miller DeVito continuum of interpersonal and Word of Mouth model's Ian Safko. This is a quantitative study using associative effects among variables Knowing, Confidence, and Buying behavior. Thus research uses semantic differential scale with a student population of information technology at a private university in Jakarta with a simple sample about 92 people as the random sampling model. From this survey results that there is influence between the level of confidence to communicate in social media purchasing behavior student, but very small. Equation that there is a Y (buying behavior) = 0.136 + 1.16 X1 (Confidence) + 0.049 X2 (Knowing). Keywords: internet, social media, interpersonal communication, word of mouth